Corporate social responsibility disclosure: Perspectives from sell-side and buy-side financial analysts. Issue 1 (6th March 2017) - Krasodomska, Joanna; Cho, Charles H.
Abstract : Purpose: The purpose of this study is to examine the usage of non-financial information related to corporate social responsibility (CSR) issues from the perspective of sell-side analysts (SSAs) and buy-side analysts (BSAs) employed in Poland-based financial institutions. Design/methodology/approach: The authors conducted a survey among financial analysts with the use of the computer-assisted telephone interview (CATI) method and an online questionnaire. The adopted methods included purposeful, quota sampling and snowball sampling. Findings: Results indicate that financial analysts make use of CSR disclosures very rarely and attribute little importance to such information. Despite the limited use of CSR information and negative assessments of its quality, respondents are in favor of making a more frequent use of CSR disclosures. Finally, except for an analyst's attitude toward the "comparability in time" information characteristic, results do not indicate any significant differences between SSAs' and BSAs' responses. Research limitations/implications: The limited number of questionnaires prevented the use of more sophisticated statistical methods and the formulation of conclusions that could apply to the entire population. In addition, although the adopted CATI method provides a number of advantages, it also has its limitations – interviews had limited time and the questions along with the answers had to take into account the respondents' limited perception ability. Practical implications: The results of this study suggest that CSR disclosures have limited usage for financial analysts, at least in the Polish context. Further, not only do respondents rarely make use of CSR disclosures but they also give low assessments to their quality. This implies that the concept of CSR remains relatively far from becoming a priority; hence, some measures and incentives may be necessary. Originality/value: The paper adds to a relatively small number of studies that have dealt with the issue of non-financial information and its usefulness for SSAs and BSAs in Central and Eastern Europe.